A study on the perceptions of University of the Philippines Diliman College of Science faculty members on the use of open access journals - Tadique, Rocelle S.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
The increasing costs of traditional print journals prompted publishers and users to find new ways to publish journals in cheaper ways. With the advent of the use of the Internet as a tool for disseminating information, the open access movement was initiated and intensified. The main goal of the movement was to publish articles online for free to the public worldwide. The results were the publication of open access journals, which were voluntarily published by the authors, were peer-reviewed, and were free for accession and use by the end users.
Faculty members and/or scholars are the main users of open access journals. Since most of the open access journals were in the sciences, the faculty members of the College of Science in the University of the Philippines, Diliman were selected as respondents of the study. This study focused on the acceptability, as well as awareness, extent of use and accessibility of open access journals to faculty members in the sciences.
A total of 140 faculty members of the College of Science served as the sample for the College Science. A questionnaire was developed to answer the problem of the study. Percentage and average method were used to analyze the data. A structured interview was also given to librarians to gauge the possible benefits and challenges of having open access journals as part of the collection.
The findings revealed that: (a) the faculty members of the College of Science are aware of the existence of open access journals; (b) open access journals are accessible in the College of Science but some barriers exist; (c) the faculty members of the College of Science use extensively open access journals in their teaching and research works; (d) there is a high level of acceptance of open access journals from the faculty members of the College of Science; and (e) the adoption of open access journals as part of the library collection can increase the library collection and can immediately provide materials to the needs of the clients of the library.
Recommendations include the conversion of research outputs of College of Science faculty members as open access journals, training of library staff and addition of computers to facilitate access of open access journals, and inclusion of other open access forms like books in the library collection.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman College of Science -- Faculty; Electronic journals -- Use studies